Identification and implication of the Islamic banks exposure to market risks:evidence from Malaysia - Kassim, Salina H. (s.n, 2012)
This study attempts to provide empirical evidences on the impact of financial shocks on the Islamic banks vis-a-vis the conventional banks. Based on the Malaysia experience over two major financial crises, namely the 1997 Asian financial crisis and the 2007 US sub-prime crisis, the study aims to test the validity of the proposition that the Islamic banks are more resilient to the financial shocks compared to the conventional banks